Giant coronary artery aneurysms in a 12-week-old infant with incomplete Kawasaki disease. (28th March 2018) - Guile, Lucy; Parke, Simon; Kelly, Alison; Tulloh, Robert
Abstract : Kawasaki disease (KD) is an acute inflammatory vasculitis that occurs worldwide and disproportionately affects male children, most commonly between the ages of 6 months and 5 years. KD can present with only a few features and thus be difficult to diagnose, particularly in the youngest and oldest patients. We describe a 12-week-old Caucasian female infant who presented with rash and fever but no other features of KD, who developed giant coronary artery aneurysms. Considering how common is the presentation of a febrile infant with a rash, this case highlights the importance of considering KD early in the differential diagnosis for any infant with unexplained fever. Furthermore, it emphasises how echocardiography can help in the investigation of a febrile child with no clear source of infection.